2021
DOI: 10.1007/s13146-021-00723-8
|View full text |Cite
|
Sign up to set email alerts
|

Water–rock interactions in a karst aquifer located in southwestern Tamaulipas, Mexico

Abstract: Water availability is fundamental for regional socioeconomic development, particularly in arid and semi-arid regions with recurrent periods of drought. Such is the case of the southwest region of Tamaulipas, whose only viable source of water is the Tula-Bustamante aquifer. This study aims to model groundwater evolution in the area, defining water-rock interaction processes, using nonparametric statistical tools and hydrogeochemical analysis. Two main processes that give rise to different hydrogeological units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The water-rock interaction has a significant time effect on the mechanical parameters of rocks, and its effect varies for different rocks [21][22][23]. It was found that an aqueous environment with higher OH − concentration causes a significant increase in the growth rate of quartz fracture [24,25]. The weathering and dissolution of many mudstone minerals are caused by the reaction of pyrite with acids in the environment during oxidation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The water-rock interaction has a significant time effect on the mechanical parameters of rocks, and its effect varies for different rocks [21][22][23]. It was found that an aqueous environment with higher OH − concentration causes a significant increase in the growth rate of quartz fracture [24,25]. The weathering and dissolution of many mudstone minerals are caused by the reaction of pyrite with acids in the environment during oxidation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%